Evaluation of Newly Developed Easy-Open Assistive Devices for Pneumatic Tube System Carriers for the Reduction of Work-Related Musculoskeletal Disorders. (8th January 2021) - Chien, Tzu-I; Liang, Huey-Wen; Lee, Ya-Fen; Liu, Fei-Yun; Hsu, Chi-Kwang; Liu, Shao-Tseng; Lee, Mo Siu-Mei; Wei, Pin-Fei
Abstract : Musculoskeletal disorders may affect labor efficiency, cause disability, impair one's work ability, and lower one's quality of life. This consequently leads to a larger expenditure of medical resources. We aimed to design easy-to-open assistive devices for pneumatic tube systems to improve ergonomics and reduce musculoskeletal complaints of workers. We followed a design control process, including designs of motors, gears, sensors, and V-shaped connecting rods. Efficacy was evaluated by examining risks based on job strain index, user satisfaction, and musculoskeletal complaints of operators before and after the system's implementation on a Nordic musculoskeletal questionnaire. We designed three assistive devices: two semiautomatic and one automatic. Each semiautomatic device costs about 300 US dollars and required space of 10 × 18 × 38   c m 3 . The automatic device costs about 3000 US dollars and required space of 28 × 38 × 50   c m 3 . The job strain index score decreased from 36 (very high risk) to 3 (low risk) with the semiautomatic devices and to 0 with the automatic device. Musculoskeletal complaints in the neck and upper limbs were reduced, with a significantly higher satisfaction rate for female operators. Our novel design of an automatic cap opening device for a pneumatic tube system was effective in improving ergonomics and reducing musculoskeletal complaints.